Analisis Peran Kepemimpinan dalam Meningkatkan Kinerja Tim di Lingkungan Kerja Multikultural pada Kota Baubau - Nurdan, Nurdan; Gazalin, Junaid; Nurlia, Nurlia; Fadli, Fadli; Irfan, Irfan (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research aims to analyze the role of leadership in improving team performance in a multicultural work environment in Baubau City. In the midst of the diversity of cultures and backgrounds that exist, leadership has a strategic role in creating synergy between different individuals, so that it can increase team productivity and effectiveness. The method used in this research is a qualitative approach using interview and observation techniques to explore the perceptions of leaders and team members regarding the influence of leadership on team performance. The research results show that leadership that is inclusive, communicative and based on the values ​​of mutual respect is very influential in improving team performance, especially in managing existing cultural differences. This research provides insights for leaders in multicultural work environments to optimize their role in building effective teamwork, which in turn contributes to achieving organizational goals.